Sound and vision in the opening titles of Māori-language television news: A multimodal analysis of cultural hybridity - Middleton, Atakohu (Te Kaharoa, 2021)
Māori are the indigenous people of Aotearoa New Zealand. British settlers arrived in the 19th century with their tradition of the newspaper, and this led to a thriving Māori-language press. Today, news in te reo Māori, the Māori language, is delivered by television, radio and the internet, harnessing the conventions of Anglo-American journalism to tell stories of indigenous preoccupations (Fox 2002). The cultural hybridity that results (Grixti 2011) is particularly marked in the opening titles of Māori-language news. The musical and visual tropes of news-show mythmaking that present the news as sites of power, truth and authority are married to representations of Māori identity and beliefs to speak to a necessarily bicultural audience (A. Middleton 2020). In this paper, a multimodal approach is employed (Bignell 2002; Machin 2010; van Leeuwen 2012), which uses frame-by-frame analysis of speech, scripts, images and music to reveal the semiosis or sign processes in play in the opening titles of the country’s top-rated English-language news bulletin, 1 News, and those of the two Māori-language television news bulletins, Te Karere and Te Kāea. Analysis reveals that 1 News titles employ the sign systems common to their counterparts across Anglophone countries in the way they promote themselves as credible, all-seeing authorities. While the titles of Māori-language news opening titles retain many of the same tropes and signposts in order to be understood as a news show, they also weave in cultural references deeply embedded in Māori language and culture to represent themselves as news by and for Māori rather than the dominant culture.